Latar Belakang Perkembangannya dan Urgensi Memahami Qira’at dalam Al Qur’an - Deden Suparman; Nurin Fatnata (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Qira'at is a field that studies how to fulfill the sentences of the Koran and the differences based on a person's origin. While a Muqri' is a person who is skilled in qiroat by narrating it by speaking, a person who is an expert in qiroat and has memorized the Qur'an should not be called a Muqri' if he does not speak sequentially about these matters. However, novice readers, also referred to as al-Qari' al-Mubtadi', are people who can explain one to three of the existing qira'at. Apart from that, the seven letters that comprise the Arabic language are Quraish, Huzail, Saqif, Hawazin, Kinanah, Tamim, and Yemen, each of which contains the meaning of the Al-Qur'an. Umar, Abu Bakr, and the Prophet Muhammad read these seven letters. After that, when Mushab Usman was created, the reading of the Koran only consisted of one letter, namely the Quraysh language. According to Ustam, reading the Qur'an with seven letters was only to eliminate the hardships and hardships that existed in the early days, and the need for it has disappeared. By aggregating and homogenizing the population around one letter or one language, the motivation is strong to eliminate elements that differentiate reading. Usman's friends did not agree with this policy. With this agreement, Ijma' occurred, and Usman had carried out great wisdom by publishing the Usmani Al-Qur'an, which united and reassured the people.